Mixed convection heat transfer in a square lid-driven cavity filled with Alsub2Osub3 - water nanofluid - Taamneh, Yazan (Strojniški vestnik, 2017)
This work is focused on the steady laminar mixed convection flow in a lid-driven square cavity filled with Alsub2Osub3 water-nanofluid using computational fluid dynamics. The top lid of the cavity was kept at a higher temperature in comparison with the bottom wall and moving at a constant speed while the left and right walls were kept insulated. Simulations were performed using Fluent ver. 6.3 where the water based nanofluid was considered as a single phase. A parametric study was conducted, and the effects of the Richardson number (0.1 </- Ri </- 10), the volume fraction of the nanoparticle (0 </- fi </- 0.04) on the fluid flow, and heat transfer inside the cavity were investigated. It was found that when (1 </- Ri </- 10) the average Nusselt number increases accordingly for the whole range of solid volume fraction of the nanofluid. The simulation results showed that the presence of nanoparticles in the base fluid increases the heat transfer rate. The variations of isotherm and streamline patterns inside the cavity with different volume fractions of nanoparticle and Richardson number were discussed and demonstrated.
Keywords: CFD; mešana konvekcija; nanofluidi; nanotekočine; ogrevan pokrov; pravokotna kotanja